Morphologic and optical characterization of ZnO:Co thin films grown by PLD - Vuichyk, M.V.; Tsybrii, Z.F.; Lavoryk, S.R.; Svezhentsova, K.V.; Virt, I.S.; Chizhov, A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
The morphological properties of the surface and optical characteristics of
nanocomposite ZnO:Co structures grown on substrates of monocrystalline silicon and
sapphire by pulsed laser deposition (PLD) method have been studied. The influence of
thermal annealing on formation of characteristically developed surface of films has been
analyzed. The experimental transmission and reflectance spectra in the visible region
have been measured. In the framework of the dielectric function, the optical constants n
and k and dispersion parameters of oscillators that provide the best fit with experimental
data have been obtained. From the infrared reflectance spectra of ZnO:Co structures, the
frequency positions of Е₁(LO) and Е₁(ТО) optical phonons have been determined. It
gives a possibility to suppose that the obtained films possess the wurtzite structure.